2013
DOI: 10.1055/s-0032-1328138
|View full text |Cite
|
Sign up to set email alerts
|

Patient expectations, outcomes and satisfaction: related, relevant or redundant?

Abstract: Study design: A prospective case series of patients undergoing lumbar spine surgery.Objective: Is there a correlation between patients' expectations before lumbar surgery, postoperative outcomes, and satisfaction levels?Methods: A prospective study of 145 patients undergoing primary, single-level surgery for degenerative lumbar conditions was conducted. Oswestry Disability Index, back Visual Analog Scale (VAS), and leg VAS were assessed preoperatively and at 6 weeks and 6 months after surgery. Patients' expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 9 publications
0
35
0
1
Order By: Relevance
“…8,13 Patient expectations have been studied for lumbar stenosis. 9,10,21 Lutz et al reported that patients with better expectations from their surgery had better outcomes after discectomy for disc herniation. 11 In contrast, McGregor and colleagues reported that patients undergoing spinal stenosis surgery frequently had unrealistically high expectations from their surgery and tended to have lower levels of satisfaction; 14,15 similarly, Toyone et al reported that patients with spinal stenosis tend to have more unrealistic and, consequently, unfulfilled expectations.…”
mentioning
confidence: 99%
“…8,13 Patient expectations have been studied for lumbar stenosis. 9,10,21 Lutz et al reported that patients with better expectations from their surgery had better outcomes after discectomy for disc herniation. 11 In contrast, McGregor and colleagues reported that patients undergoing spinal stenosis surgery frequently had unrealistically high expectations from their surgery and tended to have lower levels of satisfaction; 14,15 similarly, Toyone et al reported that patients with spinal stenosis tend to have more unrealistic and, consequently, unfulfilled expectations.…”
mentioning
confidence: 99%
“…The methodological characteristics of the articles found are similar, with 16 observational studies (9)(10)(13)(14)(18)(19)(20)(21)(22)24,26,(30)(31)(32)(33)(34) ; six prospective cohorts (25,(27)(28)34,(36)(37) ; one retrospective cohort (38) , one quasi-experimental study (35) , and one experimental study (29) . The use of instruments occurred in the immediate preoperative period in 21 studies that assessed patients' expectations (10,14,(18)(19)(20)(21)(22)(23)(24)(25)(26)(28)(29)(30)(31)(32)(33) , whereas in two studies it occurred when the patient received the indication of surgical treatment (9,27) , one study used them in the intermediate preoperative period (13) ; finally, one study completed the instrument after the patient underwent a spine surgery (34) . Three catego...…”
Section: Resultsmentioning
confidence: 64%
“…The studies were published between 1998 and 2015 and, in general, publications on this subject increased in the last five years (9)(10)14,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) . The methodological characteristics of the articles found are similar, with 16 observational studies (9)(10)(13)(14)(18)(19)(20)(21)(22)24,26,(30)(31)(32)(33)(34) ; six prospective cohorts (25,(27)(28)34,(36)(37) ; one retrospective cohort (38) , one quasi-experimental study (35) , and one experimental study (29) . The use of instruments occurred in the immediate preoperative period in 21 studies that assessed patients' expectations (10,14,(18)(19)(20)(21)(22)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations